HANDLING DAMAGE TO THE KEDATON BUILDING OF THE SULTANATE OF TERNATE - Hendra Fauzi (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2025)
The various problems that have arisen in the Kedaton Ternate building are very complex, including mechanical, physical, and chemical damage. This damage can be caused by various factors, one of which is the age of the building, which is hundreds of years old. In addition, the lack of regular maintenance due to financial constraints has also worsened the condition of the building. The last maintenance was carried out by the government of the Republic of Indonesia in 1981, and since then, no conservation work has been done on the building for the past 41 years. With the building getting older (built in 1811, last renovated in 1981), the condition of the building has deteriorated significantly, including a decline in the quality and structure of the building, which could threaten the preservation and safety of the palace's occupants. Therefore, it is important to immediately rehabilitate the Kedaton Kesultanan Ternate area in order to save the occupants, who are the Sultan/King's family, and to preserve the cultural heritage of Kedaton Kesultanan Ternate. The work began with coordination between the Sultanate and the Central Jakarta and North Maluku Regional Settlement Infrastructure Agency (BPPW) to determine the planning team and conduct a survey of the condition of the Ternate Palace to identify the necessary repairs. The handling of damage inside the building began with reviewing each existing damage, analyzing its causes, and determining the appropriate repair methods with several options that minimize risks and are in accordance with conservation principles. Every step taken must adhere to strict conservation principles and be carried out with caution to avoid further damage. Therefore, this project requires intensive coordination with relevant competent parties to avoid mistakes in handling and ensure the preservation of the historical and cultural value of the Kedaton. Regular maintenance of the building is very important, as it can help detect damage early on before it develops into more severe damage. Severe damage can have various impacts, such as endangering the safety of occupants, damaging or destroying historical and cultural value, and increasing rehabilitation costs significantly. In addition, repairs carried out at a later stage require very careful and meticulous handling. Technically, the difficulty faced is how the implementing contractor can carry out the rehabilitation in accordance with the established procedures and regulations. This is done by compiling planning drawings that are communicative, clear, and well-structured to facilitate the implementation of repairs. Meanwhile, the non-technical difficulties faced are the challenges in finding replacement materials that are close to the original building materials. These replacement materials require prior testing to determine their content and quality so that they match the original materials used in the building.